Isolation and identification of Rhizomucor pusillus from rhinofacial mucormycosis in a diabetic patient. Issue 3 (September 2014) - Bala, Kiran; Chander, Jagdish; Handa, Uma; Punia, Rajpal Singh; Raj, Rishi; Aggarwal, Salil
Abstract : Introduction: Mucormycosis is usually an invasive mycotic disease caused by fungi in the class Mucormycetes. It often occurs in immunocompromised patients but sporadic cases without apparent immune impairment have been described. Case presentation: Here we report a case of rhinofacial mucormycosis due to Rhizomucor pusillus in a 55‐year‐old diabetic female. She presented with diabetic ketoacidosis and nasal obstruction, nasal discharge and right‐sided cheek swelling following sinus surgery, which had been performed at a private hospital 1 month previously. Endoscopic biopsy was performed and the sample was sent for histopathological examination and KOH wet mount, which showed broad, pauci‐septate hyphae with right‐angle branching. The tissue was inoculated onto Sabouraud dextrose agar and white mycelial growth was obtained which turned grey with age. Morphological identification confirmed it as Rhizomucor pusillus . In vitro antifungal susceptibility testing was performed by means of the microbroth dilution method according to CLSI Approved Standard M38‐A. The isolate was found to be susceptible to amphotericin B, itraconazole and posaconazole but resistant to voriconazole and echinocandins. Functional endoscopic sinus surgery was performed and local necrotic tissue was debrided. The patient was put on liposomal amphotericin B, with a successful outcome. Conclusion: Early diagnosis is critical in prevention of morbidity and mortality associated with disease.